Bibliometric analysis of research publications in the Journal of National Science Foundation of Sri Lanka between 2010 and 2019 - Johoran, S. Shabnam (The Library, University of Colombo., 2020)
Bibliometric analysis of 358 research articles published in the Journal of the National Science Foundation of Sri Lanka was carried out by considering 40 issues published during 2010-2019. Year-wise distributions of papers, authorship pattern and degree of collaboration between authors have been analyzed. Only the research articles (358) in 40 issues were selected and others were excluded from the study. The data were collected manually from the Journal published online in the Sri Lanka Journals Online. The data were analyzed using MS-Excel 2013 software package. The results demonstrated that the highest number of research articles (54) were published in 2018. Out of 358 research publications, 335 articles (93.6%) were multi-authored and only 23 articles (6.4%) were single-authored. In 2013, there was no single-authored publication. The highest number of multi-authored articles (50) were published in the year 2018. The years 2018 and 2019 were significant in producing more number of multi-authored articles. The average Degree of Collaboration is 0.93 from 2010 to 2019, and it clearly shows that there is a high level of collaboration between the authors. Out of 358 research articles, 230 articles (64.25%) were published by Sri Lankan authors, 42 articles (11.73%) were published by Sri Lankan authors collaborated with international authors and 86 articles (24.02%) were published only by international authors. It seems that there was a minimal collaboration of Sri Lankan authors with foreign authors. Authors from 28 countries have contributed to this journal, and the highest amount of author contribution is from Pakistan with 37 publications followed by the United States and India with 12 publications each. The study revealed that the majority of the research contribution is from Sri Lankan authors and multi-authored publications, and there is a high degree of author collaboration. This study may help those who wish to map the bibliometric patterns of journals.
Keywords: Bibliometric analysis, National Science Foundation, Sri Lanka, Journal, Authorship pattern, Degree of collaboration